Isolation, Identification, and Antibiotic Resistance, CRISPR System Analysis of Escherichia coli from Forest Musk Deer in Western China - Kaiwei Yang; Xi Wu; Hui Ding; Bingcun Ma; Zengting Li; Yin Wang; Zexiao Yang; Xueping Yao; Yan Luo (Microorganisms)
Escherichia coli (E. coli) is an opportunistic pathogen widely distributed in nature, and multi-drug resistance (MDR) E. coli has been widely recognized as a critical reservoir of resistance genes, posing severe health threats to humans and animals. A total of 288 E. coli strains were isolated and purified from fresh fecal samples of forest musk deer collected from farms in Sichuan, Shaanxi, and Yunnan Provinces of China between 2013 and 2023. This study aimed to conduct antibiotic susceptibility testing and resistance gene detection on the isolated forest musk deer-derived E. coli, analyze the correlations between them, investigate the presence of CRISPR systems within the strains, and perform bioinformatics analysis on the CRISPR systems carried by the strains. Results showed that 138 out of 288 E. coli strains were MDR, with the highest resistance to tetracycline (48.3%), cefalexin (45.1%), and doxycycline (41.7%). Prevalent genes were tetA (41.0%), sul2 (30.2%), blaTEM (27.1%), with 29 gene–phenotype pairs correlated. CRISPR system-negative strains had higher resistance rates to 16 antibiotics and lower detection rates only for aac (6′)-Ib-cr, qnrA, and qnrB compared to CRISPR system-positive strains. Regional analysis showed that the problem of drug resistance in Sichuan and Shaanxi was more serious, and that the detection rate of antibiotic resistance genes was relatively high. This study guides E. coli infection control in forest musk deer and enriches resistance research data.